The River in Tuvan paremics: imagery and symbolism (against the background of the Central Asian paremiological continuum) - Lomakina, Olga V.; Nikolaeva, Elena K.; Seliverstova, Elena I.; Gishkaeva, Luisa N. (The New Research of Tuva, 2024)
The article analyzes Tuvan paremics with a river component, collected through a continuous sampling from lexicographic sources (proverb collections). These paremics that refer to rivers, water, are part of a group of units that verbalize the natural landscape code of a culture. The metaphorical interpretation of rivers, their depth, width, and strength is based on ancient ideas about the power of nature among different peoples. The analyzed paremics show the unity and strength of the people, illustrating the collective origins of an ethnos. They also provide examples that characterize a person's character and intellectual abilities. It is demonstrated that the symbolism of the motherland and the importance of one's native places in relation to rivers is widely shared. Tuvan examples are compared to similar proverbs from Altai, Khakass, and Buryat.
Keywords: paremic; proverb; linguistic culture; Tuvan language; Tuvan folklore; natural landscape code of culture; river